A comment on monetary policy and rational asset price bubbles - Franklin Allen; Gadi Barlevy; Douglas Gale (Federal Reserve Bank of Chicago, 2023)
Galí (2014) showed that a monetary policy rule that raises interest rates in response to bubbles can paradoxically lead to larger bubbles. This comment shows that a central bank that wants to dampen bubbles can always do so by raising interest rates aggressively enough. This result is different from the Miao, Shen and Wang (2019) comment on Galí's paper. They argue Galí's model contains additional equilibria in which more aggressive rules dampen bubbles. We show that for these equilibria, more aggressive rules involve threats to raise interest rates more than actual rate increases.
Keywords: 330; bubbles; monetary policy; interest rate rules; lean versus clean; General Aggregative Models: Neoclassical; Business Fluctuations; Cycles; Financial Markets and the Macroeconomy; Monetary Policy; Asset Pricing; Trading Volume; Bond Interest Rates